Design of dv/dt Filter for Insulation Protection in SiC Inverter-Fed Motor Drive Systems - Choi, Hye Won; Bae, Yun Jae; Kang, Yong Jin; Park, Cheol Hyun; Lee, Kyo Beum (Transactions of the Korean Institute of Electrical Engineers, 2024)
This paper proposes design of dv/dt filter for insulation protection in SiC inverter-fed motor drive systems. The SiC inverter is subjected to voltage and current surges. It may cause additional losses in the motor, insulation failure, high bearing current, and electromagnetic interference. To mitigate these problems, a high value of gate resistance is placed at the gate driver; however, it introduces additional switching losses on the devices. In this paper, the filter is injected between the inverter and the motor system. The characteristics of each filter such as rising time, peak voltage, and dv/dt are analyzed to ensure the national electric manufacturers association (NEMA) standard. The proposed design scheme of the dv/dt filter is demonstrated by various experimental results.
Keywords: Bearing currents; Current surges; Design of dv/dt filter; Insulation failures; Insulation protection; Inverter fed motors; Motor drive system; Motor insulation; SiC inverte; Voltage surges; Design of dv/dt filter; Insulation protection; Motor drive system; SiC inverter